The SAGE handbook of special education - Florian, Lani (SAGE, 2014)
This comprehensive, research-based work, brings together scholarship on an international level, and covers topics that transcend national boundaries. It will become essential reading for all professionals ad academics with any interest in this important and dynamic field.